Confessions of a little black gown eaudiobook - Boyle, Elizabeth (Bachelor Chronicles, 2020)
She spied him in the shadows . . . And in an instant, Thalia Langley knew the man before her was no saint. He might claim to be the Duke of Hollindrake's unassuming country cousin, but no man that handsome, that arresting, could be anything but . . . well, he simply must be an unrepentant rogue. His cat-like grace and power leave Tally shivering in her slippers at the notion of all the wicked, forbidden things he might be capable of doing . . . to her. Indeed, Lord Larken is no bumbling vicar, but a master spy there in his majesty's service to find—and murder—a notorious pirate freed in a daring prison escape. Devoted to the Crown, Larken's not about to let an interfering (and not entirely innocent) Mayfair miss disrupt his ruthless plans. Yet how can he be anything but tempted by this lady in a little black gown . . . a dress tantalizing enough to lead even Larken astray.